Invasive monitoring of blood pressure: a radiant future for brachial artery as an alternative to radial artery catheterisation? - Lakhal, Karim; Robert-Edan, Vincent (Journal of Thoracic Disease, 2017)
The arterial catheter provides reliable measurements of arterial blood pressure (BP), even in the event of minimal or absent pulsatility as observed during low flow states, cardiopulmonary bypass or extracorporeal membrane oxygenation treatment. Abrupt changes in BP are instantly and accurately detected with beat-to-beat invasive BP monitoring. Repeated sampling of arterial blood is made easy by the arterial catheter. BP waveform analysis (respiratory variation of the pulse pressure, for instance) may guide fluid management (1). Cardiac output can be determined from the BP signal, via user-friendly devices (2). For all these reasons, invasive monitoring of BP with an arterial catheter is standard practice during major surgery and severe critical illness (3).